Ali je populacija pribe Vanellus vanellus na Ljubljanskem barju pred zlomom? - Tome, Davorin (Acrocephalus, 1998)
The comparison has shown that on 49 kms large surface of Ljubljansko barje there bred, in 1998, only 25% of all of the Northern Lapwings counted in the same area during Northern Lapwings counted in the same area during 1990-1992. In spite of some documented cases of highly negative impacts of intensive farming on the population of this species, no true reasons for such changes can be exposed ...
Keywords: ornitologija; bird; ptice; Ljubljana Marshes; Ljubljansko barje; priba; Râmnicu Vâlcea